Formulasi Teoretis: Mencari Kebenaran Holistik dalam Filsafat - Arfandi Arfandi (Jurnal Pendidikan Islam Indonesia, 2016)
Knowledge always have subject, it is know, because without ability impossible there is knowledge. If there is subject of course there is object, that something as for understand or will understand. Without object, impossible there is knowledge. Truth theoretically is “ congruity in idea and expression that real consist”. Human being can’t transform holistic knowledge is personal can be control and subjugate al ammarah desire until can’t unauthorized and reins. This matter iterrelated with all of honesty, in a universal can be result intuitive from intellect and reality. There requisites person to develop truth holistic knowledge; 1. Morality subject, 2. Good intellect and 3. Qualification.